Strengthening Oral Health and Oral Hygiene Behaviour among School-Aged Children through the Healthier Smiles Phase 7 Programme: Results of an End-line Assessment in North Luwu and East Luwu Regencies, South Sulawesi, Indonesia - Andi Alim; Arlin Adam; Roberth Edison Nufninu; Zamli; Syamsul Bahri (International Journal of Health Sciences, 2026)
Oral health problems among school-aged children remain a major public health challenge in Indonesia, particularly in rural areas where access to dental care services is limited. This study aimed to evaluate the achievements of the Healthier Smiles Phase 7 Programme through an end-line assessment, focusing on changes in oral health knowledge, attitudes, and practices, the strengthening of the school environment, and programme sustainability. A mixed-methods approach with a non-experimental repeated cross-sectional design was employed, integrating quantitative surveys, school observations, Key Informant Interviews (KIIs), and Focus Group Discussions (FGDs). A total of 544 respondents, comprising 250 students, 250 parents or caregivers, and 44 teachers from 12 schools, participated in the study. The findings demonstrated that students' knowledge increased from 64.4% to 84.0%, while positive attitudes reached 98.4%. The programme also strengthened supervised toothbrushing activities, school-based health education, collaboration with community health centres (Puskesmas), and the implementation of the School Health Programme (Usaha Kesehatan Sekolah—UKS). However, healthy behavioural practices did not fully correspond with the improvement in knowledge, indicating the need for sustained reinforcement through support from families, schools, and local government. It is concluded that the Healthier Smiles Phase 7 Programme has contributed to improving oral health and oral hygiene behaviours while strengthening the school health system. Nevertheless, sustaining these achievements requires stronger policy support and continued cross-sectoral collaboration.